An eLearning program to prepare residents for a rotation in pediatric emergency medicine: A qualitative study. Issue 6 (November 2022) - Tyebally, Arif; Dong, Chaoyan
Background: To meet ACGME-I (Accreditation Council for Graduate Medical Education–International) training and duty hour requirements, we converted our 3-week-long pediatric emergency medicine induction program to an eLearning program. Objectives: The study aimed to identify areas of the eLearning program residents perceived useful and the components that helped them prepare for clinical work. Methods: The qualitative study took place in a tertiary pediatric emergency department. Twenty-seven residents from family medicine, emergency medicine, and pediatric medicine participated in focus group discussions to explore how they perceived the eLearning program helped prepare them for work. The interviews were audio-recorded, and transcripts were analyzed and coded into categories and themes. Results: Four themes emerged from the data analysis: residents' access to the eLearning program, instructional methods, eLearning design elements, and supplementary learning. Residents valued autonomy to control their pace of learning and use online features that matched their preferred learning styles. Design features such as the use of questions and quizzes helped stimulate learning, but attention had to be paid to the order of questions in the modules and the format of the questions. Written guidelines served as a good reference for learners and face-to-face sessions accompanying the eLearning program helped reinforce knowledge and offered opportunities to interact with faculty members to clarify questions. Conclusion: Systematic planning focusing on access, instructional methods, and design is essential when creating eLearning programs for residency training. eLearning programs can be enhanced by the incorporation of team-based learning and having accompanying written content to reference.